2021
DOI: 10.3390/land10030319
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Different Governance Modes and Marketization Performance for Collective Commercial Construction Land in Rural China?

Abstract: The collective commercial construction land (CCCL) reform in China has attracted considerable attention worldwide, but studies on the influencing factors and performance of governance modes for CCCL marketization are still in their infancy. First, by deconstructing CCCL, this study developed a conceptual framework from the perspective of transaction cost economics. Based on a series of surveys, interviews, and closed questionnaires in two pilot areas, this study determined the influencing factors for governanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Theoretical analysis finds that the marketization of collective commercial construction land changes the status quo that only state-owned construction land can attract investment and develop industries, which realize rural land value and share more land benefits with farmers and consequently boost rural industrial revitalization and farmers' affluence (Yan et al, 2021). From the perspective of transaction costs, Chen et al (2021) explore the effect of the marketization of collective commercial construction land on promoting rural industry development and village collective income under different governance structures. Some studies, on the other hand, use village cases from the perspectives of land marketization and property rights conversion to reveal the positive effects of capital resources on the countryside and urban-rural factor flows on rural development and gentrification (Kan, 2021).…”
Section: The Relations Between Rural Land Governance and Rural Revita...mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical analysis finds that the marketization of collective commercial construction land changes the status quo that only state-owned construction land can attract investment and develop industries, which realize rural land value and share more land benefits with farmers and consequently boost rural industrial revitalization and farmers' affluence (Yan et al, 2021). From the perspective of transaction costs, Chen et al (2021) explore the effect of the marketization of collective commercial construction land on promoting rural industry development and village collective income under different governance structures. Some studies, on the other hand, use village cases from the perspectives of land marketization and property rights conversion to reveal the positive effects of capital resources on the countryside and urban-rural factor flows on rural development and gentrification (Kan, 2021).…”
Section: The Relations Between Rural Land Governance and Rural Revita...mentioning
confidence: 99%
“…From the perspective of transaction costs, Chen et al. (2021) explore the effect of the marketization of collective commercial construction land on promoting rural industry development and village collective income under different governance structures. Some studies, on the other hand, use village cases from the perspectives of land marketization and property rights conversion to reveal the positive effects of capital resources on the countryside and urban‒rural factor flows on rural development and gentrification (Kan, 2021).…”
Section: Theoretical Basis For Analysing Land Self‐organization For R...mentioning
confidence: 99%
“…Y. Li’s (2009) research on farmers in Guangdong Province posits that in market transactions, the farmland transfer contract is not notarized, and the intervention of village cadres in farmland transfer greatly increases the uncertainty of farmers’ behavior in farmland transfer(Hu et al, 2021), which in turn increases transaction costs. Some scholars found that the transaction costs of farmers’ search for information, price negotiation and contract signing (Z. Chen, Zhuo, et al, 2021), supervision, and performance have a significant negative impact on the transfer of farmland.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars found that the transaction costs of farmers' search for information, price negotiation and contract signing (Z. Chen, Zhuo, et al, 2021), supervision, and performance have a significant negative impact on the transfer of farmland. Studying farmland transfer and contract selection from the perspective of transaction costs is a recent academic effort (J.…”
Section: Introductionmentioning
confidence: 99%
“…Among them is the American ACSI model, which has been chosen by an increasing number of researchers in the field of research on measuring satisfaction in China for its strengths in combining the most representative of customer satisfaction theories, namely: the expectation-difference theory, perceived performance theory, and equity theory [19,20]. Most of the existing studies on the market entry of collective-owned commercial construction land focus on the development of legal systems [21,22], the improvement of the value-added revenue distribution system [23,24], and the construction of a unified urban-rural land market [25], which all focus on the macro-level of the legal system and planning. This is not conducive to the accurate judgement and identification of farmers' true feelings towards the market entry of collective-owned land and its influencing factors, and it is not possible to obtain the effect of the implementation of policy on the ground.…”
Section: Introductionmentioning
confidence: 99%